2013
DOI: 10.1097/jto.0b013e318299243b
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life and Utility in Patients with Advanced Non–Small-Cell Lung Cancer: A Prospective Cross-Sectional Patient Survey in a Real-World Setting

Abstract: The results presented indicate a substantial impact of lung cancer on patients' HRQOL, with stage IV disease, line of treatment, and PD, resulting in considerable deterioration of utility. The values obtained here will inform evaluations of cost-utility for NSCLC therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
110
3
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(122 citation statements)
references
References 19 publications
(18 reference statements)
3
110
3
3
Order By: Relevance
“…In accordance with the findings from this survey, high rates of anxiety/depression have been reported in patients with advanced nonsmall cell lung cancer [23], rheumatoid arthritis [24,25] and severe asthma [26]. Moreover, a negative impact of chronic disease on patients' mental function [24,27], role, emotional or social functioning [24,28,29], and both the intensity and quality of sexual relationships [30] has been described.…”
Section: Implications For the Future Management Of Pahsupporting
confidence: 69%
“…In accordance with the findings from this survey, high rates of anxiety/depression have been reported in patients with advanced nonsmall cell lung cancer [23], rheumatoid arthritis [24,25] and severe asthma [26]. Moreover, a negative impact of chronic disease on patients' mental function [24,27], role, emotional or social functioning [24,28,29], and both the intensity and quality of sexual relationships [30] has been described.…”
Section: Implications For the Future Management Of Pahsupporting
confidence: 69%
“…Lung cancer patients, particularly those in an advanced stage, suffer from poor physical condition, which often negatively affects their quality of life 13. A recent study conducted on non-small-cell lung cancer (NSCLC) patients suggested that lung cancer with stage IV disease, higher line of treatment, and more progressive disease substantially impacted patient quality of life 20. Poor quality of life may cause various psychiatric disorders, including depression.…”
Section: Discussionmentioning
confidence: 99%
“…The utility scores of PFS and survival after progression were obtained from previously published studies (Table 2) [44, 45]. The reported disutility caused by SAEs was also considered in the current analysis [44].…”
Section: Methodsmentioning
confidence: 99%